Coarse-Grained Monte Carlo Simulations of Graphene-Enhanced Geopolymer Nanocomposite Nucleation - Mohammadreza Izadifar; Neven Ukrainczyk; Eduardus Koenders (Nanomaterials)
Geopolymer nanocomposites, incorporating pristine graphene-based nanomaterials, are at the forefront of research in advanced construction materials, improving mechanical, electrical, and thermal properties. This study investigates the nucleation mechanisms of geopolymers on pristine graphene substrates, namely graphene-reinforced geopolymer nanocomposites (GRGNs), by analyzing nanostructure particle sizes, pore size distributions, cluster sizes, and system energy at a pH of 11, compared to a system without graphene nanosheets. Seven distinct monomer species were selected to observe cluster evolution over numerous iterations, providing insights into the dynamic nature of geopolymer nucleation on graphene-based substrates. Thus, the computed adsorption energies, based on recent DFT studies, reveal interactions between aluminosilicate species and graphene nanomaterials. Furthermore, the implementation of energy values from dimerization reactions among monomer species, as reported earlier, introduces tetrahedral geometrical constraints, crucial for understanding how particles aggregate into clusters. The key findings indicated that (4.34%) fewer particles participate in cluster formation in the system containing a graphene nanosheet compared to the one without it. However, the system with the graphene nanosheet exhibits (1.65%) more favorable energy. This contrast is due to the weaker adsorption energy on the graphene nanosheet (heterogenous nucleation) than in homogenous particle nucleation. The complete dissolution of MK required (4.54%) more iterations in the system with graphene than in the system without it. This research underscores the significant potential of geopolymer nanocomposites and their role in shaping the future of construction materials.